The effect of postnatal morphine exposure on spinal processing of sensory inputs - Platten, Amy (2025)
Neonates and children differ from adults in pain processing, particularly in descending pain pathways, which mature from facilitatory to inhibitory during a critical period in postnatal development. Opioid exposure has been shown to accelerate this maturation process. Therefore, this study aims to further understand the effect of postnatal morphine exposure using immunohistochemistry to analyse markers in rat spinal cord dorsal horns. We examined primary afferent termination patterns, mu opioid receptor (MOR) expression, markers parvalbumin (PV), and protein kinase C gamma (PKCγ), and explored potential sex-specific interactions. We hypothesised that, following morphine exposure there would be an increase in PV and MOR intensity, but no significant changes in primary afferent termination. Our findings showed a significant elevation of IB4 intensity in male rats following morphine exposure, but no significant differences in MOR intensity. Morphine exposure revealed an increased neuronal cell count in PV labelling area for females, and an increased PKCγ total intensity in male rats. Overall, this study demonstrates that exposure to opioids during critical periods of postnatal development can influence nociceptive markers later in life, with sex differences, highlighting the importance in the inclusion of both sexes in pain and opioid research